Determinants of patient satisfaction in outpatient musculoskeletal physiotherapy: a systematic, qualitative meta-summary, and meta-synthesis. Issue 4 (13th February 2020) - Rossettini, Giacomo; Latini, Teresa Maria; Palese, Alvisa; Jack, Susan M.; Ristori, Diego; Gonzatto, Serena; Testa, Marco
Abstract: Purpose: To identify and synthesise patient-identified factors that influence satisfaction with outpatient musculoskeletal physiotherapy (O-MSK). Methods: A systematic, qualitative meta-summary and meta-synthesis was conducted by accessing six electronic databases: CINAHL, Embase, MEDLINE, Scopus, Web of Science, and Wiley Online Library, from inception to March 2017. Additional studies were identified by using a "berry-picking" method. Search limits were: primary studies; English language; and involving human subjects. Qualitative peer-reviewed articles describing patient satisfaction in O-MSK were eligible for inclusion. Two reviewers critically appraised eligible studies independently using the critical appraisal of skills programme tool for qualitative studies. Extracted verbatim data of included studies were synthesised using the meta-summary and meta-synthesis by using a purpose-designed form. Results: Eleven studies were included in the article. Factors influencing patient satisfaction were grouped into six broad themes: 1) clinical outcomes; 2) physiotherapist features; 3) patient features; 4) physiotherapist-patient relationship; 5) treatment features, and 6) healthcare setting features. Conclusions: These findings suggest that patient satisfaction in O-MSK is a multidimensional construct influenced by individual patient/provider, clinical, and contextual factors. Future reviews should include a synthesis of findings from both qualitative and quantitative studies to establish a fully comprehensive understanding of this complex health phenomenon. Implications for rehabilitation: Patient satisfaction in outpatient musculoskeletal physiotherapy is affected by different factors, thus reflecting a multidimensional construct; Single determinants are not sufficient to affect patient satisfaction; Patient satisfaction is influenced individual patient/provider, clinical outcomes, and contextual factors; Further studies should be designed to investigate the relationships among these factors.